The View Point behind Appraisal in Discourse Study - Agung Budi Kurniawan (Concept : Community Concern for English Pedagogy and Teaching, 2018)
Appraisal is one of discourse study or analysis component. The point of appraisal is about personal expression to a phenomena or object. One aspect which give much influence to appraisal is context. Context has significant rule for a participant to apply his or her appraisal. Context is about psychological view point to the situation and facts faced by a participant. Every participant could give different interpretation context to a similar phenomenon or object. The components of appraisal consist three things which are attitudes, amplification, and source. The attitude is about personal feeling of a participant. Amplification is about how strong of a participant’s feeling to an object. Source is about the starting point of our personal expression. The rule and use of appraisal could make our verbal and non verbal communication become very communicative, effective, and efficient if it is applied appropriately. Key Words: View Point, Appraisal, Discourse